Analisis Manajemen Strategi Pemasaran dan Sumber Daya Manusia PT.Garuda Indonesia Branch Office Solo Dalam Menghadapi Pandemic Covid-19 di Bandar Udara Adi Soemarmo Solo - Neddy Faturrahman (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the management of marketing strategies and human resources at PT. Garuda Indonesia Branch Office Solo so as not to experience losses during the Covid-19 Pandemic. Qualitative method with primary and secondary data. The results of the research on marketing strategies and human resources are implementing a marketing strategy in collaboration with agents, hospital laboratories and conducting special prices. The human resource strategy develops human resources in special lessons related to marketing, operational activities in the face of a pandemic & RULS (Recurrent Uplifting Learning Service) with the performance of maintaining good relations with partners and evaluating the progress of marketing and flight operations. Establish HR in 2021 which establishes units for marketing, finance and operational divisions by reducing human resources that are less professional, reducing human resources that are less interested/competent.